Enhanced mesoscale partitioned modelling of heterogeneous masonry structures. (29th January 2018) - Minga, E.; Macorini, L.; Izzuddin, B. A.
Summary: This paper presents an accurate and efficient computational strategy for the 3‐dimensional simulation of heterogeneous structures with unreinforced masonry components. A mesoscale modelling approach is employed for the unreinforced masonry parts, whereas other material components are modelled independently with continuous meshes. The generally nonmatching meshes of the distinct domains are coupled with the use of a mesh tying method. The physical interaction between the components is captured with the use of zero‐thickness cohesive interface elements. This strategy enables the optimisation of the individual meshes leading to increased computational efficiency. Furthermore, the elimination of the mesh compatibility requirement allows the 3‐dimensional modelling of complex heterogeneous structures, ensuring accurate representation of each component's nonlinear behaviour and their interaction. Numerical examples, including a comparative analysis on the elastic and nonlinear response of a masonry bridge considering arch‐backfill interaction and the nonlinear simulation of a multileaf wall, are presented to show the unique features of the proposed strategy and its predictive power in comparison with experimental and numerical results found in the literature.